Charisma & female expressiveness: language, ethnoculture, politics - Петлюченко, Наталя Володимирівна; Петлюченко, Н. В.; Петлюченко, Наталья Владимировна; Petliuchenko, Natalia V.; Petlyuchenko, Natalia; Чернякова, Валерія Олексіївна; Чернякова, В. О.; Чернякова, Валерия Алексеевна; Cherniakova, Valeriia O.; Chernyakova, Valeria (Trnava : University of SS Cyril and Methodius, 2019)
This paper represents a contrastive analysis of the verbal and paraverbal (prosodic and gesture) features of expressive female political speech in Latin America, Spain, and Ukraine. The language corpus consisted of public speeches delivered by Spanish-speaking female politicians Eva Peron, Christina de Kirchner, and Manuela Carmena, and Ukrainian female politicians Lesya Orobets, Iryna Farion, and Yulia Tymoshenko, who are attributed political charisma in public discourse. The article includes an overview of theoretical approaches to female speech studies and follows current trends in modern sociolinguistics, which, on the one hand, accumulate the classical methodology of studying the gender-related specifics of oral female speech based on social standing, age, and professional affiliation, and on the other hand, reflect the latest approaches to the contrastive analysis of socio-political discourse both in the Spanish-Speaking World (Spain and Latin America) and in Ukraine. We offer a novel method of multimodal analysis for studying voice and kinetic means of the expressive speech of female politicians in Spain, Latin America, and Ukraine. This allows determining the ethnospecific correlates of expressiveness in the speech of female politicians at the verbal and paraverbal levels and building an updated model of female charismatic expressiveness based on the integrity of its verbal and paraverbal categories. Charismatic rhetoric originates in political communication in times of crisis and is characteristic of politicians whose stand is not consistent with the majority position. Charismatic enthusiasm and inspiration are ethnically colored and are reflected in prosodic and gesture emphasis accompanying both independent and dependent parts of speech indicating the autonomy of charismatic rhetoric as a model. The results of this research can be used in discourse studies, applied phonetics, comparative linguistics, and political communication.

У цій роботі представлено контрастний аналіз вербальних та паравербальних (просодичних і жестових) особливостей експресивного жіночого політичного мовлення в Латинській Америці, Іспанії та Україні. Мовний корпус складався з публічних виступів іспаномовних політиків Єви Перон, Крістіни де Кіршнер та Мануели Кармена та українських політиків Лесі Оробець, Ірини Фаріон та Юлії Тимошенко, яким у публічному дискурсі приписують політичну харизму. Стаття містить огляд теоретичних підходів до вивчення жіночого мовлення та відслідковує сучасні тенденції сучасної соціолінгвістики, які, з одного боку, акумулюють класичну методологію дослідження гендерної специфіки усного жіночого мовлення на основі соціального статусу, віку та професійну приналежність, а з іншого боку, відображають новітні підходи до контрастивного аналізу суспільно-політичного дискурсу як в іспаномовному світі (Іспанія та Латинська Америка), так і в Україні. Ми пропонуємо новий метод мультимодального аналізу для вивчення голосових і кінетичних засобів експресивного мовлення жінок-політиків Іспанії, Латинської Америки та України. Це дозволяє визначити етноспецифічні кореляти експресивності у мовленні жінок-політиків на вербальному та паравербальному рівнях та побудувати оновлену модель жіночої харизматичної експресивності на основі цілісності її вербальних та паравербальних категорій. Харизматична риторика зароджується в політичній комунікації під час кризи і характерна для політиків, позиція яких не відповідає позиції більшості. Харизматичний ентузіазм і натхнення мають етнічне забарвлення і відображаються в просодичних і жестових акцентах, що супроводжують як самостійні, так і залежні частини мови, що вказує на автономність харизматичної риторики як зразка. Результати цього дослідження можуть бути використані в дослідженнях дискурсу, прикладної фонетики, порівняльного мовознавства та політичної комунікації.
Petlyuchenko N. Charisma & female expressiveness: language, ethnoculture, politics / N. Petlyuchenko, V. Chernyakova // Lege artis. Language yesterday, today, tomorrow. - Vol. 4. - Issue 1. - Trnava : University of SS Cyril and Methodius, 2019. - P. 83-132.
Keywords: charisma; gender; contrastive analysis; political discourse; expressive female speech; verbal; paraverbal; prosodic; gesture; Latin America; Spain; Ukraine; харизма; гендер; контрастивний аналіз; політичний дискурс; експресивне жіноче мовлення; вербальне; паравербальне; просодичний; жест; Латинська Америка; Іспанія; Україна; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics